ANALISA FAKTOR YANG BERPENGARUH PADA MOTIVASI BELAJAR BAHASA INGGRIS MAHASISWA JURUSAN PARIWISATA BUDAYA - Md. Yudyantara Risadi; Luh Kompiang Sari; Ni Luh Putu Uttari Premananda (UHN IGB Sugriwa Denpasar, 2022)
The aim of this research was to find out the factors affecting the students’ English learning motivation in culture tourism department State Hindu University I Gusti Bagus Sugriwa Denpasar. It also aimed to find out which motivation contributes more on students’ English achievement. The research used qualitative method by providing questionnaire consisting of 20 statements. The questionnaire used Likert Scale. The sample was saturated sampling. The data acquired then was calculated by using statistical procedure and elaborated in descriptive way. The result proved the extrinsic motivation had more significant contribution towards students’ English learning motivation. The findings also revealed that extrinsic motivation in which quality of the teacher and teaching learning used and the module was the prominent factors that can sustain the students’ motivation in the class. Thus, the quality of the teacher and module must be the priority to maintain students’ motivation in the classroom